Os trabalhadores portuários avulsos (TPAS) e os impactos socioeconômicos da Lei 8.630/93 de modernização dos portos - Souza, Gracineide Maria de (2017)
This dissertation is intended to measure the socioeconomic impact caused to the Dock Workers by the enactment of Law 8.630/93, of February 25, 1993, known as the Modernization of Ports Act, which influenced several productive and professional segments. The Law mandated the institutionalization of the Labor Management Body in Espírito Santo (OGMO-ES), the body responsible for administering the activities developed by the Port Workers, in a process that changed the labor relations of these categories. Such a change was so profound that it became the object of this dissertation: the identification of the impact to these workers from the begging of the OGMO`s administration. For this purpose, a survey was carried out with 31 (thirty-one) port workers, trade union 3 (three) leaders, the superintendent of the administrative body of the Port of Vitória, CODESA, and a worker whose activities were terminated because of the changes implemented by said Law. As a theoretical framework, specialized bibliography and case studies, that refer to the theme, the use of oral history techniques used to build memory sources, as well as other documentary sources. The methodology used to obtain information on workers and unions was a questionnaire with 24 (twenty-four) questions, 20 closed questions, 3 (three) semiopen and 1 (one) open, applied to 31 (thirty-one) port workers Different categories and structured interviews directed to some union leaders and CODESA. From the studies carried out with the workers and the analysis of the current scenario of the activities that are developed in the movement of cargo in the ports, it was possible to identify the various socioeconomic impacts experienced by the category and the trade union entities.